TO OPTIMIZATION OF THE INDEPENDENT KIND OF ACTIVITY OF STUDENTS OF A MEDICAL UNIVERSITY - Marasulov , A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
It is proposed to develop an automated computer-based training system for self-integrated training of students of a medical university, based on: building a structural-functional system of synchronized differential connections of lectures and practical classes in the main disciplines of the Department of Biomedical Engineering, Informatics and Biophysics with the disciplines of natural science, general professional and clinical departments, respectively; defining and establishing sets of integration systems of these disciplines already implemented to date; creation of an integrated educational and methodological knowledge base and a database of these disciplines and a navigation system on it; creation of a functionally, task-oriented structural-logical system for the formation of the content of education, contributing to the comprehensive implementation of typical functions and tasks of the professional activity of a specialist in a medical university; the development of a new integration system of disciplines, taking into account the presented biomedical problem; development of a computer-teaching system for managing students’ own educational activities and the educational process of the departments of a medical university; creation of a local interdepartmental network of links between the disciplines being taught; development of special software for information and communication technology of independent integrated teaching of students of a medical university.